Welfare Losses of Road Congestion - Antonio Russo; Martin W. Adler; Federica Liberini; Jos N. van Ommeren (Center for Economic Studies and ifo Institute (CESifo), 2019)
We estimate the marginal external congestion cost of motor-vehicle travel for Rome, Italy, using a methodology that accounts for hypercongestion (a situation where congestion decreases a road's throughput). We show that the external cost – even when roads are not hypercongested – is substantial, equaling about two thirds of the private (time) cost of travel. About one third of this cost is borne by public transport users. Most roads are never hypercongested, but some are hypercongested for more than one hour per day. Hypercongestion accounts for about 40 percent of congestion-related welfare losses. Welfare losses incurred on roads that are hypercongested are substantial, predominantly because of a reduction in speed rather than throughput. Our results suggest policies that reduce congestion can result in important welfare gains.
Keywords: D62; R41; H23; 330; marginal external congestion cost; deadweight loss; hypercongestion; public transport